2017
DOI: 10.1080/08958378.2017.1282065
|View full text |Cite
|
Sign up to set email alerts
|

Effects of inhaled aerosolized carfentanil on real-time physiological responses in mice: a preliminary evaluation of naloxone

Abstract: This study examined the real-time exposure-response effects of aerosolized carfentanil (CRF) on opioid-induced toxicity, respiratory dynamics and cardiac function in mice. Unrestrained, conscious male CD-1 mice (25-30 g) were exposed to 0.4 or 4.0 mg/m of aerosolized CRF for 15 min (Ct = 6 or 60 mg min/m) in a whole-body plethysmograph chamber. Minute volume (MV), core body temperature (T), mean arterial blood pressure (MAP) and heart rate (HR) were evaluated in animals exposed to CRF or sterile HO. Loss of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 39 publications
2
20
0
1
Order By: Relevance
“…During and following exposure to aerosolized carfentanil, we observed prolong periods of both bradypnea and apnea in our animal model, as well as reductions in duty cycle which is consistent with the respiratory depression seen in both humans and other animal models [ 3 , 22 , 44 ]. Naloxone treatment was able to significantly reduce the number of both bradypneic and apneic events following administration.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…During and following exposure to aerosolized carfentanil, we observed prolong periods of both bradypnea and apnea in our animal model, as well as reductions in duty cycle which is consistent with the respiratory depression seen in both humans and other animal models [ 3 , 22 , 44 ]. Naloxone treatment was able to significantly reduce the number of both bradypneic and apneic events following administration.…”
Section: Discussionsupporting
confidence: 87%
“…Ferrets have been utilized in medical research as models of respiratory function and used to investigate respiratory pathogens like influenza and severe acute respiratory syndrome-associated corona virus, mainly because of similarities between ferret and human upper and lower respiratory tracts, pathogenesis, and symptoms [ [33] , [34] , [35] ]. We observed that ferrets were more sensitive to the effects of carfentanil than previously studied rodent models [ 3 , 36 ] and that exposure to carfentanil produced severe apnea and prolonged incapacitation in ferrets, which suggests that ferrets have a closer approximation of opioid intoxication in humans when compared to mice. Treating with naloxone following exposure significantly reduced the total time the animals were incapacitated and reduced the apneic periods.…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…Animal models and studies in humans support the use of higher doses of naloxone for reversal of opioid overdoses involving synthetic opioids. For example, small animal models suggest lack of clinical reversal may occur with fentanyl analogues at doses which previously reversed morphine toxicity [14]. Furthermore, animal models also suggest that the reversal of fentanyl toxicity by naloxone is dose dependent [15].…”
Section: Main Textmentioning
confidence: 99%